Determining The Profitability of Palm Oil Companies: The Role of Exchange Rate Volatility, Crude Palm Oil Prices, and Inflation as Moderating Variables - Devita Eka Wardani; Selvi; Mohamad Agus Salim Monoarfa (Transbahasa, 2026)
Profitability is one of the primary indicators used to assess corporate financial performance, particularly in the palm oil industry, which is highly dependent on macroeconomic conditions and the dynamics of the global commodity market. This study aims to examine the effect of exchange rate volatility and Crude Palm Oil (CPO) prices on corporate profitability, with inflation serving as a moderating variable, among palm oil companies listed on the Indonesia Stock Exchange during the 2019–2024 period. This study employed a quantitative approach using secondary data obtained from corporate financial statements and relevant macroeconomic data. The sample consisted of 24 palm oil companies, resulting in 144 observations. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) to examine both the direct effects of the independent variables and the moderating role of inflation. The findings indicate that exchange rate volatility and CPO prices have a positive but statistically insignificant effect on corporate profitability. Furthermore, inflation is unable to moderate the relationship between exchange rate volatility and profitability or between CPO prices and profitability. However, when considered simultaneously, all independent variables collectively exert a significant effect on profitability. These findings suggest that macroeconomic factors jointly contribute to the financial performance of palm oil companies, although firm-specific internal factors remain the primary determinants of profitability. The results are expected to provide useful insights for corporate managers, investors, and policymakers in formulating strategies to improve corporate resilience and financial performance amid changing economic conditions.